Energy Value of Yield and Biomass Quality in a 7-Year Rotation of Willow Cultivated on Marginal Soil - Mariusz Jerzy Stolarski; Stefan Szczukowski; Michał Krzyżaniak; Józef Tworkowski (Energies, 2020)
Bioenergy plays a major role as a renewable energy source in the European Union. Solid biomass is derived mainly as wood from forests and wood processing plants. Willow plantations set up on marginal lands can be a supplementary source of wood for energy generation. This study aimed to determine the energy value of yield and the thermophysical properties and elemental composition of the biomass of 7-year rotation willow harvested on marginal soil. Three varieties and three clones were cultivated in the Eko-Salix system on three marginal soils in northern Poland: riparian, alluvial soil, classified as heavy complete humic alluvial soil (Obory); organic, peat–muck soil formed from peat (Kocibórz); very heavy mineral clay soil (Leginy). Favourable conditions for obtaining high energy value biomass were at Kocibórz and Obory with a high groundwater level. The energy value of biomass at Leginy was lower than at Kocibórz and Obory (by 33% and 26%, respectively). The Ekotur variety had the significantly highest yield energy value (217 GJ ha−1 year−1) among the varieties and clones under study. This feature at Kocibórz and Obory was 288 and 225 GJ ha−1 year−1, respectively, and 139 GJ ha−1 year−1 at Leginy. Moreover, the biomass of this variety contained less ash (1.1% d.m.), sulphur (0.03% d.m.) and nitrogen (0.28% d.m.), which is beneficial from the energy-use perspective. Notably, the yield energy value of the UWM 095 clone biomass was also high (167 GJ ha−1 year−1). This study showed that willow grown in the Eco-Salix system can be a significant source of energy contained in good-quality woody biomass.